A COMMUNICATIVE STYLES IN ENGLISH MEETING - Sri Rahayu Juniati Rahayu Juniati (Jurnal Ilmiah Administrasita', 2019)
There are four skills that should be students or people know in learning English. They are listening, reading, speaking and writing. Speaking is one of skill that many people quite difficult to do because some of them feel nervous or anxious so that they would not know what shoul they say. English meeting is one of place that facilitate the students or people to increase their speaking English proficiency. When they speak, they use a communication strategies to reduce their nervous. Therefore, in this study will investigate the communicative styles that they use. This study aim to find out the dominant communicative style used in English meeting and explore how the speakers communicative style influence their achievement in acquiring English. This paper is based on recorder that taken from one of English meeting club in STISIP Muhammadiyah Sinjai called YES (Younger English of STISIP Muhammadiyah Sinjai). To collect data, the researcher recorded the English meeting activity. The recording was obtained, transcribed, and analyzed by using discourse analysis. The communicative styles used was discussed based on the communciative styles of Mahmud (2017). The finding shows that the speakers utilise the communicative style in speaking. Their communicative style involves of speech acts, discourse markers, language choices, address terms and the inclusion of regional terms derived from the Bugis- Sinjai language such as additional –mi, -ji. Finding of this study are useful in process of learning English that occur in English meeting in which there will be various expression that are produced by the speakers in English meeting.